Kandungan gizi dan Organoleptik Sie Reuboh dengan Penambahan Cuka Aren (Arenga pinnata) dan Daun Jeruk Purut (Citrus hystrix) pada Konsentrasi yang Berbeda - Masyitah, Masyitah; Arief, I. I.; Suryati, T. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
This research aimed to study and evaluate the nutritional composition of sie reuboh treated with different concentrations of palm vinegar (Arenga pinnata) and kaffir lime leaves (Citrus hystrix) addition. The four treatments for sie reuboh were P0 (0 mL palm vinegar and 0 kaffir lime leaves), P1 (100 mL palm vinegar and 10 kaffir lime leaves, P2 (100 mL palm vinegar and 10 kaffir lime leaves). The parametes are nutrition content (water content, ash content, fat content, protein content and carbohydrates content) and organoleptic (hedonic qualiy test and hedonic test). The result showed that different concentrations of palm vinegar and kaffir lime leaves addition significantly affected (p<0.05) ash content and carbohydrates content of sie reuboh. Ash content in this study ranged from 3.11 % to 2.43 % and carbohydrates content ranged 3.89 % to 5.59 %. The result of organoleptic showed that were significantly affected (p<0.05) on hedonic quality test (flavor of palm vinegar, flavour kaffir lime leaves and taste). The value of palm vinegar flavor has 3.17 to 3.83, the value of kaffir lime leaves has 3.00 to 3.57 and the taste value has 3.30 to 3.77. Different level of palm vinegar and kaffir lime leaves not affected at moisture content, protein content, fat content, hedonic quality (color and tenderness) and hedonic (color, flavor, taste, tenderness and overall appearance).